The COL5A1 gene: A novel marker of endurance running performance - Posthumus, M.; Schwellnus, M. P.; Collins, M. (Medicine & Science in Sports & Exercise, 2011)
Background: Running economy, a key component of endurance ability, has been shown to be associated with flexibility. Increased stiffness (inflexibility) may improve running economy and therefore endurance running ability. The COL5A1 gene, which encodes the a1-chain of type V collagen, was found to associate with measures of flexibility. Type V collagen is a quantitatively minor fibrillar collagen, which is believed to regulate fibrillogenesis within tendons and other connective tissue.